BUSINESS: Fears on 'danger' worker rights: First Edition (Coventry evening telegraph, 2002)
Local MEP Philip Bushill-Matthews, Conservative spokesman for employment and social affairs, said: "Never before have I had four separate business visitor groups in four days on the same subject. It shows their extreme concern about this dangerousdirective."